Quantitative Assessment of Oysters’ Multiple Nitrogen Removal Pathways in a Subtropical Bay - Rongxin Liu; Qixing Ji; Zhengping Chen; Heng Zhang (Journal of Marine Science and Engineering)
Oyster aquaculture helps mitigate coastal eutrophication by assimilating organic nitrogen for biomass and by denitrification in both the oyster digestive tract and sediment below. Efforts are needed in the quantitative assessment of oysters’ multiple nitrogen removal pathways at large-scale aquaculture sites, especially removal in oyster bodies, which has been much less quantified among these pathways. This study takes a subtropical estuary (Shenzhen Bay in South China) as a testbed to conduct laboratory rearing experiments and field investigation. The laboratory results show that an oyster individual of harvest size can remove 0.59 mg-N day−1 through denitrification within the body, which can be proportionally extrapolated to 4.6 kg-N km−2 day−1 in Shenzhen Bay. Assimilating field measurements into a “flux inventory model” yields the oyster-induced total nitrogen removal of Shenzhen Bay as 33.3 kg-N km−2 day−1, in which biomass harvest, denitrification in oysters, and sediment contributed 26%, 14%, and 60%, respectively. Additionally, the oyster’s filter-feeding lifestyle exports nitrogen from the water column to the sediment, which can contribute to ~3% of the daily nitrogen input into the bay. This study confirms the potential of oyster nitrogen removal, especially within the body, and provides a working framework for quantitative assessment of coastal nitrogen removal by the growing scale floating oyster aquaculture.